2009
DOI: 10.1097/scs.0b013e31819ba1c1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of the Topography and Distribution of the Posterior Superior Alveolar Artery

Abstract: The aim of this study was to clarify the arrangement of the anatomic courses and distribution of the intraosseous branch (IObr) of posterior superior alveolar artery. The anatomic variations in the topographic relationships were described to provide beneficial data to minimize injury to the IObr during surgical procedure of the buccal wall of the maxillary sinus. The IObrs in 42 hemifaces of embalmed Korean cadavers were examined. The courses of the IObr of the posterior superior alveolar artery were classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
78
3
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 18 publications
17
78
3
3
Order By: Relevance
“…25 Another study, aiming to identify the branches of the maxillary artery, did not provide information on the prevalence within the sinus lateral bony wall. 26 One more report was discarded because it reported surgical information from a series of cadaveric material, 13 and five articles describing a prevalence of 100% of PSAA within the sinus wall, based on anatomical dissections, were also excluded from this metaanalysis 6,7,11,25,27 (Table 1). Finally, another paper was discarded because CT scans were performed to investigate sinus disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Another study, aiming to identify the branches of the maxillary artery, did not provide information on the prevalence within the sinus lateral bony wall. 26 One more report was discarded because it reported surgical information from a series of cadaveric material, 13 and five articles describing a prevalence of 100% of PSAA within the sinus wall, based on anatomical dissections, were also excluded from this metaanalysis 6,7,11,25,27 (Table 1). Finally, another paper was discarded because CT scans were performed to investigate sinus disorders.…”
Section: Resultsmentioning
confidence: 99%
“…2 As accidental blood vessel damage may cause massive bleeding, 3 careful surgical planning is paramount, 3,4 particularly because the intraosseous anastomosis between the posterior superior alveolar artery (PSAA) and the infraorbital artery (IOA) has been linked to potential haemorrhagic complications. 5,6 The intraosseous branch of the PSAA within the lateral sinus wall usually describes a straight or U-shaped course, 7 forming a concave arch whose closest point to the osseous crest is located near to the first molar. 8,9 This anastomosis supplies the Schneiderian membrane, periosteum, and the anterolateral sinus wall, 6-10 while contributing to graft integration and healing of the surgical wound.…”
mentioning
confidence: 99%
“…Ella et al [8] reported the anastomosis to be located 3-13 mm from the edge of the lower alveolar. In a paper published by Hur et al [10], the mean distance between the intraosseous anastomosis and the cervical line was 26.9 mm at the level of the first premolar, 24.1 mm for the second premolar, 21.1 mm for the first molar, 22.4 mm for the second molar, and 23.3 mm from the maxillary tuberosity. In the Rysz et al study [16], the distance between the anastomosis and the cervical line of the first molar was 15-19 mm.…”
Section: Discussionmentioning
confidence: 99%
“…In both of arches, it means that the restorative treatment by implants depends on the quantity and quality of residual bone, because of the presence of two noble anatomical structures: alveolar canal in the inferior jaw and the maxillary sinus in the upper jaw. The principal surgical technique to gain a height augmentation is the sinus floor lift procedure, with a lateral approach [4][5][6][7][8][9][10][11][12]. In this procedure, the knowledge of the vascular supply of this region is mandatory, to avoid unwanted haemorrhagic complications and to guarantee a good vascularisation of the grafted material [2,3,5].…”
Section: Discussionmentioning
confidence: 99%
“…51,52 İntraoperatif ve postoperatif kanama, maksiller sinüsün cerrahisinde majör komplikasyonlardan biridir. 51,53 PSAA' nın lateral duvar üzerindeki dağılımı, greft materyalinin iyileşmesine ve integrasyonuna katkıda bulunur. 54 Elian 55 ve Watanabe'de 56 çalışmalarında; maksiller sinüse uygulanan cerrahi işlemler sırasında PSAA'nın zarar görüp, önemli miktarda hemorajiye neden olabileceğini bildirmişlerdir.…”
Section: Görüntü Kalitesiunclassified